PHONOLOGICAL TRANSLATION IN THE HUNGER GAMES NOVEL: INVESTIGATING THE MEANINGS OF WORDS IN SECOND LANGUAGE ACQUISITION - Baiatun Nisa; Sulhizah Wulan Sari (Faculty of Humanities, Universitas Jenderal Soedirman, 2018)
This article discusses phonological translation in fiction text of The Hunger Games Novel translated by Hetih Rusli. This research investigates translation acquisition of transferring or replacing the Source Language into the Target Language as the second language. In analyzing the novel of The Hunger Games, the writers allude the process of translation that is produced by translator using the methods of phonological translation. The reseach used qualitative method and the data is taken from the novel of Suzanne Collins: The Hunger Games from both English and Indonesian version. The purpose of this paper is to find out the meaning of words from the Source Language into the Target Language using the method of phonological translation. Many words in the novel are commonly used in daily life of society such as the word of animal, places, and plants. From the discussion, it can be concluded that phonological translation is used in translating the Hunger Games novel. Using phonological translation could sound better and could deliver the meaning of the words itself with the play on sound. Thus, the research finds that the meanings of translation word in the Hunger Games Novel which have been analayzed in SL show the sense of original or foreign meaning in the TL. The significant of this study is to reveal the meaning of word as a languange phenomenon and communication used in daily life of society through phonological translation.